CD56 (Neural Cell Adhesion Molecule) Expression in Ovarian Carcinomas: Association With High-Grade and Advanced Stage But Not With Neuroendocrine Differentiation. Issue 2 (February 2017) - Bösmüller, Hans-Christian; Wagner, Philipp; Pham, Deborah Lam; Fischer, Anna K.; Greif, Karen; Beschorner, Christine; Sipos, Bence; Fend, Falko; Staebler, Annette
Abstract : Objective: Neural cell adhesion molecule (CD56) has been proposed as a potential marker for neuroendocrine differentiation in carcinomas, together with synaptophysin and chromogranin A. However, CD56 immunoreactivity by itself can be found in a broad variety of tumors, including ovarian neoplasms. CD56 has recently been suggested as a potential target for antibody-based therapy. However, for ovarian carcinoma, there is only limited data available regarding the pattern of CD56 immunoreactivity, coexpression of neuroendocrine markers, and correlation with histological types and clinical parameters. Methods: In our study, we therefore evaluated CD56 staining by immunohistochemistry on a tissue micrroarray with 206 ovarian carcinomas, including 151 high-grade serous, 7 low-grade serous, 32 endometrioid, 11 clear cell, 5 mucinous, as well as 33 atypically proliferating serous tumors/serous borderline tumors. Results: At least focal CD56 immunoreactivity was observed in 65% of carcinomas of all histological types. Moderate staining with at least 10% positive cells was found in 44 (28%) high-grade serous carcinomas (HGSOCs), 2 (29%) low-grade serous and 3(9%) endometrioid carcinomas. Strong immunoreactivity was limited to 10 (7%) HGSOCs. There was no correlation with the expression of chromogranin or synaptophysin. Serous borderline tumors showed only weak and focal staining in 11 (33%). Expression of CD56 overall was significantly associated with high-grade and advanced stage. In the subgroup of HGSOCs, CD56 expression was associated with reduced overall survival (median 30 vs. 47 months, P = 0.039, log rank, univariate analysis). Conclusions: CD56 (neural cell adhesion molecule) is frequently expressed in ovarian carcinomas and is significantly associated with HGSOC and advanced tumor stage. Due to its lack of correlation with neuroendocrine differentiation, CD56 expression is of limited diagnostic value, but may rather serve as a marker for tumor progression or as a potential therapeutic target.